2020
DOI: 10.3390/microorganisms8030331
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of Bacterial Growth Dynamics in Response to Growth Media by Dynamic Time Warping

Abstract: Bacterial growth curves, representing population dynamics, are still poorly understood. The growth curves are commonly analyzed by model-based theoretical fitting, which is limited to typical S-shape fittings and does not elucidate the dynamics in their entirety. Thus, whether a certain growth condition results in any particular pattern of growth curve remains unclear. To address this question, up-to-date data mining techniques were applied to bacterial growth analysis for the first time. Dynamic time warping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…E. coli colonies growing on agar media can suitably mimic the ecosystem of microbes living on solid surfaces. Our previous studies experimentally and theoretically demonstrated the coordination of genome reduction and population growth in liquid media [ 21 , 22 ], as well as changes in growth due to nutritional conditions [ 22 , 23 ]. The reported E. coli strains and the corresponding media were adopted in the present study to investigate whether and how genome reduction and nutritional decline caused any changes in colony size variation and the rule of spatial distribution.…”
Section: Introductionmentioning
confidence: 99%
“…E. coli colonies growing on agar media can suitably mimic the ecosystem of microbes living on solid surfaces. Our previous studies experimentally and theoretically demonstrated the coordination of genome reduction and population growth in liquid media [ 21 , 22 ], as well as changes in growth due to nutritional conditions [ 22 , 23 ]. The reported E. coli strains and the corresponding media were adopted in the present study to investigate whether and how genome reduction and nutritional decline caused any changes in colony size variation and the rule of spatial distribution.…”
Section: Introductionmentioning
confidence: 99%
“…[ 20 ] However, this growth curve is based on the theoretical fitting of the model, and specific growth conditions will lead to different growth curves. [ 21 ] The experiment conducted revealed that the optical density value of the bacterial suspension dropped rapidly at the beginning of the culture. This was mainly because the bacterial liquid was a mixture of sludge and microorganisms at the beginning of the culture, with many impurities and excessive interference, and the microorganisms were partially dead in the process of adapting to the environment.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, whether the medium and the genotype could be clustered according to the mutation and growth rates were investigated by machine learning ( Jordan and Mitchell, 2015 ), which was beneficial for discovering the dataset with unclear mechanisms relating to metabolism ( Cuperlovic-Culf, 2018 ; Kim et al, 2020 ), genetics ( Libbrecht and Noble, 2015 ; Schrider and Kern, 2018 ), evolution ( Wang et al, 2018 ) and population dynamics ( Ashino et al, 2019 ; Cao et al, 2020 ; Gilpin et al, 2020 ). Here, the support vector machine (SVM) was applied to classify the three media (i.e., LB, MAA, and M63) and the four genotypes (i.e., reduced genome, mutator, genome reduced mutator, and wild type).…”
Section: Resultsmentioning
confidence: 99%